“Accused of a Sodomy Act”: Bible, Queer Poetry and African Narrative Hermeneutics - van Klinken, Adriaan; Muyunga-Mukasa, Tom (My University, 2022)
This article explores the role of poetry and narrative methods in African-centred queer biblical studies and theology. As a case in point, it presents a poem, titled “Accused of a Sodomy Act,” by Tom Muyunga-Mukasa, that was written as part of a queer Bible reading project with Ugandan LGBTQ refugees. The poem is a contemporary re-telling of the gospel story about Jesus and the “woman caught in adultery” in the context of socio-political homophobia in Uganda. The poem is complemented by an autobiographical reflection by the writer, providing insight into his personal experiences of growing up as gay and religious in Uganda. This is embedded in a more general discussion, relating the poem to trends of life storytelling in African LGBTQ activism, and to established narrative methodologies in African theological and biblical studies scholarship. Overall, the article makes a methodological contribution, by foregrounding queer poetry and storytelling as innovations in African narrative hermeneutics that expand the established concern with gender and sexuality beyond a heterosexual framework, and that include the marginalised voices and experiences of LGBTQ people.
Keywords: LGBTQ; African queer theology; Narrative hermeneutics